Predictability in Contemporary Medicine - Ciulla, Michele M. (Frontiers in Medicine, 2021)
Medical practice, today, is increasingly under the guidance of statistical-mathematical models that are, undoubtedly, valuable tools but, at the same time, they are, by definition, partial representation of the reality. Indeed, given that the statistics may be more or less adequate, a model is still a subjective interpretation of the researcher and is also influenced by the historical context in which it operates. In this opinion I’ll provide a short historical excursus that retraces the advent of probabilistic medicine as a long process that has a beginning that should be sought in the discovery of the complexity of disease. By supporting the belonging of this evolution to the scientific domain it is also acknowledged that the underlying model can be imperfect or fallible and, therefore, confutable as any product of science. Indeed it seems nontrivial here to recover these concepts especially today where clinical decisions are entrusted to the practical guidelines, which are a hybrid product resulting from the aggregation of multiple instances including the probabilistic approach do disease. Finally, before the advent of precision medicine, by limiting the use of guide lines to the original context that is consultative, an aged approach is supported namely the relationship with the individual patient.